Alien. Covenant [videorecording (DVD)] - Fassbender, Michael, 1977-; Waterston, Katherine; Crudup, Billy, 1968- (Twentieth Century Fox Home Entertainment, 2017)
When a ship carrying two thousand humans setting out to colonize a distant planet encounters a system failure, they land on a moon and discover a race of hostile aliens.